Salvage Pancreaticoduodenectomy After Complete Response to Chemoradiotherapy for a Previously Unresectable Pancreatic Adenosquamous Carcinoma: A Case Report. Issue 6 (February 2015) - Elias, Anne; Chatzizacharias, Nikolaos A.; Xanthis, Athanasios; Corrie, Pippa; Davies, Susan; Brais, Rebecca J.; Jamieson, Neville V.; Praseedom, Raaj K.; Huguet, Emmanuel; Harper, Simon J. F.; Jah, Asif
Abstract : Abstract: Pancreatic cancer is known for its typically late presentation and poor survival rates, with overall 5-year survival of less than 5%. The role of chemotherapy alone or with radiotherapy in the management of locally advanced tumors continues to be an area of debate. We report a case of locally advanced, pancreatic adenosquamous carcinoma that was initially deemed unresectable intraoperatively. Nonetheless, the tumor was resected after radiological response to gemcitabine-capecitabine chemoradiotherapy regimen similar to the Selective Chemoradiation in Advanced LOcalised Pancreatic cancer trial. Histological examination revealed complete pathological response with extensive fibrosis (ypT0 N0). On 12-month follow-up CT, a single liver lesion in the left lateral segment was identified and confirmed to be a metastasis with cytological diagnosis via EUS and FNA. The disease remained stable and confined to the solitary hepatic metastasis after further gemcitabine chemotherapy. Therefore, a further successful resection was performed. The 2 main strategies for the management of locally advanced unresectable pancreatic cancer are chemotherapy induction followed by consolidation chemoradiotherapy or chemotherapy alone, with conflicting published evidence. Evidence for the optimal management of the rare histological type of adenosquamous carcinoma is scant. We present a case of such tumor with a complete pathological response to chemoradiotherapy. The results of future studies in the area are eagerly awaited.